(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2018)
The iron age is considered to be part of the prehistoric periodization in Malaysian Cultural History. However, until the discovery of the Sungai Batu Archaeological Complex, discoveries related to this period were extremely scarce. The earliest prehistoric iron age artifacts dated 1300 B.P. were found in Batu Kurau, Perak. Most of these discoveries consisted of complete tools and implements found in Santubong and Tembeling with unclear archaeological contexts, with the latter being the only evidence for iron smelting activity. Interpretations of these discoveries had posed some problems due to dating and chronological issues. However, with the discovery of the iron smelthing sites in Sungai Batu in 2009, our knowledge regarding Iron Age in Malaysia has become clearer. The geo-archaeological method and scientific analysis approach was adopted to study these sites, which yieded the date 535 B.C.E. This paper attempts to discuss the contributions of Sungai Batu to our present knowledge on the iron age in Malaysia. Keywords: Sungai Batu site, Kedah, iron smelting, geo-archaeology